Spatio-temporal analysis of rabies in animals in Ukraine over 2019–2023 - Ukhovskyi, V. V.; Pishchanskyi, O. V.; Korniienko, L. Y.; Rudoi, O. V.; Drozhzhe, Z. M.; Dedok, L. A.; Radzykhovskyi, M. L.; Pyskun, A. V.; Tsarenko, T. M. (Regulatory Mechanisms in Biosystems, 2024)
Rabies is an extremely dangerous zoonotic disease caused by a neurotropic virus of the genus Lyssavirus. All mammals, including carnivores and omnivores, are susceptible to this disease. Foxes, dogs, cats, and other wild and domestic animals require special attention with regard to rabies. The aim of this study is a comprehensive spatial and temporal analysis of rabies cases among animals in Ukraine from 2019 to 2023, with a focus on identifying high-risk areas and trends over time. A retrospective epidemiological analysis of rabies incidence among different animal species in Ukraine for the period 2019–2023 was conducted. Data were collected from reports of regional laboratories of the State Service of Ukraine on Food Safety and Consumer Protection, research data from the Research Institute of Laboratory Diagnostics and Veterinary and Sanitary Expertise and included confirmed rabies cases among different animal species such as foxes, cats, dogs, cattle and others. The Kernel Density Estimation (KDE) method was used to analyze the spatial distribution and intensity of rabies cases, and the directional distribution method was used to estimate the distribution and central tendency of rabies cases. Data visualization was performed using Quantum GIS software. The analysis revealed 5,405 rabies cases over the five-year period, with the highest density of cases in the Central and Northern Regions, particularly in Poltava, Kyiv, and Kharkiv oblasts. In 2020 and 2021, there was a marked spread of rabies cases to the Southern and Eastern Regions. Core density assessment maps showed consistently high levels of rabies intensity in the Central and Northern Regions, with some increase in the Southern Regions in 2020–2021. Foxes were the most affected animal species, accounting for 39.5% of cases, followed by cats (27.8%) and dogs (23.1%). The spatial and temporal analysis highlights persistent high levels of rabies in central and northern Ukraine, with new hotspots in the south and east. This study emphasizes the urgent need for targeted rabies control measures, including vaccination and monitoring, especially in identified high-risk areas. Effective rabies control requires a combination of improved diagnostic tools, affordable vaccines, and public awareness campaigns to reduce the spread of the disease among domestic and wild animals.